The Cystic Fibrosis Heterozygote Advantage: A Synthesis of Ideas - Beckett, Kristen M. (Anthropologica, 2022)
It has been proposed that the high frequency of Cystic Fibrosis (CF) is due to a selective advantage in the heterozygous state. This research supports this proposition and attempts a holistic perspective in reviewing the various models proposed. The pathophysiology, molecular and population genetics and the epidemiology are all demonstrated to be key components when evaluating the carrier advantage of CF. Various hypotheses are reviewed and critically evaluated. The most recent explanation proposed—that CF affords protection against cholera—is a main focus of this research. While this theory has been supported by molecular in vivo experiments, the historical epidemiology of both CF and cholera argue against the acceptance of this model. The conclusion is drawn that while the cholera hypothesis is attractive, further research will be necessary before it can either be accepted or rejected as the explanation for high frequencies of CF.